Association of Gestational Diabetes Mellitus With Neonatal Respiratory Morbidity. Issue 2 (February 2019) - Werner, Erika F.; Romano, Megan E.; Rouse, Dwight J.; Sandoval, Grecio; Gyamfi-Bannerman, Cynthia; Blackwell, Sean C.; Tita, Alan T.N.; Reddy, Uma M.; Jain, Lucky; Saade, George R.; Iams, Jay D.; Clark, Erin A.S.; et al.
Abstract : OBJECTIVE: To assess neonatal respiratory morbidity in pregnancies with and without gestational diabetes mellitus (GDM) at imminent risk of late preterm delivery in a modern U.S. cohort. METHODS: Secondary analysis of a randomized placebo-controlled trial in which women with singleton pregnancies at high risk for delivery between 34 0/7 and 36 5/7 weeks of gestation were allocated to betamethasone or placebo. The primary outcome for the trial and this secondary analysis was a composite outcome of neonatal respiratory morbidity in the first 72 hours of life. Secondary outcomes included neonatal severe respiratory complications, neonatal intensive care unit (NICU) admission greater than or equal to 3 days, and hyperbilirubinemia. We examined associations between neonatal morbidities and GDM status after adjustment for baseline differences and study group allocation using modified Poisson regression. Models incorporating a product interaction term between GDM status and treatment arm (betamethasone or placebo) were also evaluated. RESULTS: Of the 2, 831 women enrolled in the trial, 306 (10.8%) had GDM. Women with GDM were significantly older and were more likely to be parous and to have hypertensive disorders of pregnancy than those without GDM, but they were similar regarding race, gestational age at randomization (35.6 weeks) and at delivery (36.1 weeks), and study group assignment. Neonates born to women with GDM were no more likely to meet the primary outcome than those born to women without GDM, even after adjusting for differences in age, parity, and hypertensive disorders of pregnancy (12.1% vs 13.1%, adjusted RR 0.84; 95% CI 0.61–1.17), nor were they more likely to have severe respiratory complications or prolonged NICU admission. CONCLUSION: Maternal GDM is not associated with increased neonatal respiratory morbidity in this study population who were at high risk for late preterm birth. Abstract : Among pregnancies at high risk for late preterm birth, maternal gestational diabetes mellitus is not associated with increased neonatal respiratory morbidity.